PENGARUH JUS JAMBU BIJI (PSIDIUM GUAJAVA) TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL ANEMIA - Noviana Luthfi Jayanti; Sunarto Sunarto; Yuwono Setiadi (JURNAL RISET GIZI, 2018)
Background  : Iron deficiency anemia is a national health problem that many pregnant women experience. Based on data from Riskesdas Results of 2013, the prevalence of anemia in pregnant women is 37.1%. The rate of anemia in Central Java in 2015 reached 56.2%. The government program to overcome the incidence of iron deficiency anemia in the form of giving of Fe tablet for 90 days with dose of 60 mg, beside Fe tablet also needed to support factor of iron absorption in hemoglobin synthesis process. Guava is a food ingredient that contains micronutrients needed in the synthesis of hemoglobin such as iron and vitamin C.Objective  : To know the effect of red guava juice on hemoglobin level in pregnancy anemia.Method  : This research used pre-test post-test control group design. Samples each group as many as 11 people. Interventions performed on the treatment group giving of guava juice for 20 days in pregnant women who consumed Fe tablets, while the control group only consumed Fe tablets. The test used to know the effect of treatment on hemoglobin levels using anova repeated measure with α = 0.05.Results  : The mean increase after intervention in the treatment group was 1.1 g/dl and in the control group 0.7 g/dl. Based on the results of the anova test, there is the influence of guava juice and Fe tablet consumption on the insignificant hemoglobin level (0.439) after controlled by the intake of energy, protein, iron and vitamin C.Conclusion : Guava juice for 20 days can increase hemoglobin level by 1.1 g/dl although not statistically significant.